A Scale to Assess Religious Beliefs in End-of-Life Medical Care - Balboni, Tracy (Cancer, 2019)
BACKGROUND: Studies postulate that certain religious beliefs related to medical care influence advanced cancer patients’ end-of-life (EOL) medical decision-making and care. Because no current measure explicitly assesses such beliefs, we here introduce and evaluate the Religious Beliefs in EOL Medical Care (RBEC) scale, a new measure designed to assess religious beliefs in the context of EOL cancer care. METHODS: The RBEC scale consists of seven items designed to reflect religious beliefs in EOL medical care. Its psychometric properties were evaluated in a sample of advanced cancer patients (N=275) from Coping with Cancer II, an NCI-funded, multi-site, longitudinal, observational study of communication processes and outcomes in EOL cancer care. RESULTS: The RBEC scale proved to be internally consistent (Cronbach’s α=0.81), unidimensional, positively associated with other indicators of patients’ religiousness and spirituality (establishing its convergent validity), and inversely associated with patients’ terminal illness understanding and acceptance (establishing its criterion validity), suggesting its potential clinical utility in promoting informed EOL decision-making. Most patients (87%) reported some (‘somewhat’, ‘quite a bit’ or ‘a great deal’) endorsement of at least one RBEC item and a majority (62%) endorsed three or more RBEC items. CONCLUSIONS: The RBEC scale is a reliable and valid tool assessing religious beliefs in the context of EOL medical care, beliefs that are frequently endorsed and inversely associated with terminal illness understanding.